Pengaruh Intensitas Olah Raga Terhadap Siklus Haid Atlet - Gayatri, Sri Wahyuni; Safitri, Asrini (Wal'afiat Hospital Journal, 2022)
Exercise and moderate physical activity have many benefits for people of all ages. Physical activity or sport has a bad impact if it is done excessively, especially for women. Excessive exercise can cause hypothalamic dysfunction which causes disturbances in GnRH secretion. This causes delayed menarche and menstrual cycle disorders. The main factor causing GnRH suppression in female athletes is excessive energy use that exceeds energy intake in athletes. In addition, professional athletes tend to have lower body weight which can cause menstrual dysfunction. The purpose of the study was to determine the effect of exercise intensity on the menstrual cycle of athletes. The type of research conducted is categorical analytic with the cohort method. There is no significant relationship between the type of sport that athletes engage in with the incidence of irregular menstrual cycles with the correlation value obtained p = 0.298. There is a relationship between the frequency of exercise on the incidence of irregular menstrual cycles with a correlation value of p = 0.03. There is a relationship between the duration of exercise on the incidence of irregular menstrual cycles with a correlation value of p = 0.03. The conclusion that there is a relationship between the frequency and duration of exercise on the menstrual cycle of athletes.